2012
DOI: 10.1016/j.solmat.2012.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence imaging under applied bias for characterization of Si surface passivation layers

Abstract: In this work, we present a novel characterization technique for the analysis of Si surface passivation layers, using a photoluminescence imaging setup. In this technique the effective lifetime of passivated Si wafers is measured while applying an external bias over a rear side dielectric film. We demonstrate that this method can be used to analyze the passivation of silicon surfaces in inversion, depletion and accumulation conditions. In this paper the method is illustrated by characterization of a-SiN x :H pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The excess carrier concentration Δ was then calculated from the PL intensity averaged over the electrode area as described in Ref. 7. The steady state effective lifetime can then be calculated as…”
Section: B the Pl-v Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The excess carrier concentration Δ was then calculated from the PL intensity averaged over the electrode area as described in Ref. 7. The steady state effective lifetime can then be calculated as…”
Section: B the Pl-v Methodsmentioning
confidence: 99%
“…Another alternative, which was used in Ref. 7, is to use a known passivation layer with a low SRV on the front of the wafer, so that is dominated by recombination on the rear side. We estimate the uncertainty in the determination of to be 10%.…”
Section: B Bulk and Front Surface Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Kho et al 21 reported lifetime data, from which SRV can be extracted, for a range of carrier injections and positive dielectric charge densities, yet their proposed model parameters did not fit the experimental data. Most recently, Haug et al 27,28 proposed an original method to characterise SRV using photoluminescence (PL) imaging and a direct metal contact to the dielectric to control field effect passivation. In this method, the SRV was measured using a fixed photon flux, thus corresponding to different injections levels.…”
Section: à3mentioning
confidence: 99%
“…Although these studies provided a remarkable insight into the Si/SiO 2 interface, in particular, for the development of MOSFET technology, the D it and r p;n extracted from them have not produced an accurate characterisation of the macro-scale SRV, especially when carrier injection and dielectric charge are considered together in a broad domain. Haug 27,28 and Chen 48 have recently obtained accurate models by lumping together the D it Âr n;p product into the S p;n ðEÞ parameter, and extracting empirical values for the latter such that theory fits experimental data. Here, a similar approach is taken where S n;p values are used to find a good empirical fit of experimental SRV.…”
Section: E the Effect Of Electron And Hole Recombination In Effectivmentioning
confidence: 99%